Diagnostic Accuracy of Contrast Enhanced Computed Tomography Scan in Evaluation of Bony Erosions of Fungal Sinusitis in Immunocompromised Patients Taking Histopathology as Gold Standard - Madiha; Faiq, Syed Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Fungal sinusitis with bony erosion is serious problem in immunocompromised patients and it can cause high morbidity and mortality. Early detection is important but clinical findings are not very specific, so imaging play major role. Objective: To determine the diagnostic accuracy of contrast enhanced computed tomography scan in diagnosis of bony erosions of fungal sinusitis in immunocompromised patients taking histopathology as gold standard. Study design: Cross sectional study. Duration and place of study: This study was conducted at Department of Diagnostic Radiology, Sindh Institute of Urology and Transplantation, Karachi over a period of six months from December 20, 2024 to June 20, 2025. Methodology: Total 98 patients were included. Patient’s age 15–60 years of both genders with suspected fungal sinusitis were selected. Contrast enhanced computed tomography scan was done and findings of bony erosion were noted. After that histopathology was performed as gold standard. Data was analysed on Statistical Package for Social Sciences version 26. Results: Mean age was 36.03±13.65 years. There were 49 males 49 (50.0%) and 49 females 49(50.0%). Bony erosion on computed tomography scan was positive in 55 (56.1%) patients while on histopathology it was positive in 52 (53.1%). There were 49 true positive, 40 true negative, 6 false positive and 3 false negative cases. Sensitivity was 94.23%, specificity 86.96%, positive predictive value 89.09%, negative predictive value 93.02% and diagnostic accuracy 90.82%. Conclusion: Contrast enhanced computed tomography scan is reliable method for detecting bony erosion in fungal sinusitis in immunocompromised patients and shows good diagnostic accuracy.